Characterization of Silica Nanoparticles from Pumice as an Aerogel Adsorbent - Hidayah, Rahma; Kurniawati, Desy; Alizar, Alizar (Universitas Negeri Medan, 2023)
Pumice is often found around the banks of rivers, this stone is a type of igneous rock formed from volcanic eruptions. One of the compounds contained in pumice is silica. Therefore, the synthesis of silica nanoparticles from pumice using the sol gel method was used because it is simpler and more efficient in terms of cost and processing time. the initial step was by reacting pumice powder and NaOH at 70°C - 80°C then synthesized by adding 2M HCI to form a gel or white precipitate, soaking in ethanol, teos, hexane solutions was then synthesized to become an aerogel. Silica synthesis results into silica aerogels were characterized by FTIR and XRF. From FTIR silanol and siloxane functional groups were found, and the SiO2 composition increased to 93,299% after synthesis.